Pediatric osteoarticular infection: trend in surgically treated patients and association of methicillin-resistant Staphylococcus aureus with requirement of secondary procedures. Issue 6 (8th October 2020) - Jain, Mohit J.; Bradko, Viachaslau; Zhu, Huirong; Inneh, Ifeoma; Shinava, Vinitha R.
Abstract : Supplemental Digital Content is available in the text. Abstract : Acute pediatric osteoarticular infection demonstrates variability in both presentation and response to treatment. Many respond to antibiotics ± single operation, while some require multiple surgeries. Currently, it is difficult to predict who may require additional procedures. Infections due to methicillin-resistant Staphylococcus aureus (MRSA) have been associated with more complications. The purpose of this study is to determine MRSA trends and degree of association with the occurrence of multiple procedures. We performed a retrospective analysis of surgically treated pediatric (1 month–18 years) patients for acute osteomyelitis and septic arthritis at a tertiary children's hospital from 2003–2017. The cohort was divided into single-procedure and multiple-procedure groups. A total of 753 patients were studied with a mean age of 7.05 years (2.4 months–17.9 years). We identified 645/753 (85.6%) patients who were treated with a single-procedure and 108/753 (14.4%) patients who required multiple- procedures. The lower extremity (hip, knee, tibia, and femur) was most commonly involved. The epidemiologic trend runs almost parallel between two groups with a peak in 2009. The odds ratio for multiple-procedures was 2.0 [95% confidence interval (CI), 1.2–3.1; P = 0.002] with dual infection (osteomyelitis + septic arthritis), 2.6 (95% CI, 1.6–4.4; P = 0.001) with high-risk conditions and 4.6 (95% CI, 3.0–7.1; P < 0.001) if MRSA was present. MRSA significantly predicts the requirement of additional operative procedures for the treatment of osteoarticular infections in children. Besides clinical deterioration and other markers, the presence of MRSA can be a considerable indicator for a planned secondary-procedure. Level III retrospective cohort study.